2018
DOI: 10.3389/fendo.2018.00565
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto's Disease and Thyroid Cancer in Children: Are They Associated?

Abstract: Hashimoto's thyroiditis (HT) is the most common cause of thyroid disease in children and adolescents. Along with significant modifications of thyroid function, HT in pediatric age can be accompanied by relevant thyroid structural alterations. Over time, benign thyroid nodules, carcinoma and, rarely, primary non-Hodgkin lymphoma can develop. However, the relationships between HT and neoplasms are poorly defined. The main aim of this paper is to discuss what is presently known regarding the coexistence of HT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 47 publications
1
27
0
4
Order By: Relevance
“…Recent studies by Hosseini and Grani have also suggested the use of preoperative TgAb levels as a marker for well-differentiated thyroid cancer (21,22). Although multiple studies have reported a correlation between AITD and DTC, this relationship is still controversial (27)(28)(29). It appears that the diagnostic method used influences the association between HT and DTC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Hosseini and Grani have also suggested the use of preoperative TgAb levels as a marker for well-differentiated thyroid cancer (21,22). Although multiple studies have reported a correlation between AITD and DTC, this relationship is still controversial (27)(28)(29). It appears that the diagnostic method used influences the association between HT and DTC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 108 pediatric thyroid cancer cases, HT was detected in 28.7% of the enrolled patients [16]. Furthermore, congenital hypothyroidism caused by dyshormonogenesis or by an iodine transporter defect increases the risk of nodules in children that can evolve to thyroid cancer of the follicular type [16]. A causal association between external radiation exposure and thyroid cancer is strongly supported by epidemiologic studies, since the young thyroid gland is particularly radiosensitive.…”
Section: Risk Factors For Thyroid Nodules and Factors Indicative Of Hmentioning
confidence: 99%
“…According to the results of these studies, the frequency of PTC in children and adolescents with HT is variable, from 0.7 tõ 3%, while in patients with PTC the prevalence of coexisting HT varies from 6.3% to more than 40% of the cases. In a study including 108 pediatric thyroid cancer cases, HT was detected in 28.7% of the enrolled patients [16]. Furthermore, congenital hypothyroidism caused by dyshormonogenesis or by an iodine transporter defect increases the risk of nodules in children that can evolve to thyroid cancer of the follicular type [16].…”
Section: Risk Factors For Thyroid Nodules and Factors Indicative Of Hmentioning
confidence: 99%
“…Currently, HT is being considered the most common cause of hypothyroidism in iodine sufficient areas in both the adult and pediatric patients. Although considered benign for many years, HT proved its unfavorable evolution being involved in altering the reproductive system, influencing mental and intellectual activity, influencing other autoimmune diseases and last but not least in the occurrence of malignant processes such as PTC [12,13]. Potential causal associations between Hashimoto's thyroiditis and PTC have been studied previously and were first reported by Dailey et al in 1955, linking chronic inflammation to neoplastic changes [14].…”
Section: Background and Aimsmentioning
confidence: 99%